U.S.-Canada Trade Liberalization and MNC Production Location - Feinberg, Susan E.; Keane, Michael P. (The Review of Economics and Statistics, 2001)
Using confidential firm-level panel data from the Bureau of Economic Analysis, we examine how the bilateral trade flows of U.S. multinational corporations (MNCs) and their Canadian affiliates responded to U.S.-Canadian tariff reductions from 1983 to 1992. We find that Canadian affiliate sales to the United States are negatively correlated with Canadian tariffs, but U.S. parent sales to Canadian affiliates have little association with Canadian tariffs. These results contradict the notion that Canadian tariff reductions would lead to a ‘hollowing out’ of Canadian manufacturing. We also find substantial heterogeneity in MNC responses to tariff changes within narrowly defined manufacturing industries. Overall, bilateral trade liberalization is trade-creating, as U.S. MNCs integrated their North American production such that Canadian affiliates increased sales to the United States and reduced domestic sales.